INFORMED CONSENT - Gunawan Widjaja; Yohanes Firmansyah (Cross-border, 2021)
In Indonesia, the development of "informed consent" in a formal juridical manner, was marked by the emergence of a statement from the Indonesian Doctors Association (IDI) regarding "informed consent" through SK PB-IDI No. 319/PB/A.4/88 in 1988. Then it was reaffirmed by PerMenKes No. 585 of 1989 concerning "Informed Consent". As well as emphasized by Law No. 29 of 2004. Informed Consent obtained in an improper manner cannot be considered as the inventor of the patient's autonomy right, so that such action is a violation of the law. -Values in the local culture are very varied.